Challenges in Recruitment of Doctors by Government - Raha, Shomikho; Berman, Peter; Rao, Krishna D. (World Bank, New Delhi, 2013)
This note describes some of the problems found in recruiting new doctors to the government health care system, drawing on the recent experiences in three cases: the Central Health Service (CHS), the Uttar Pradesh (UP) government health care system and Tamil Nadu government health care system. In comparing the different experiences of recruitment in the three cases, the policy note highlights institutional issues and the incentives built into an employment package as important for further consideration in the aim to scale up the numbers of government doctors.